The role of IL-37 and IL-38 in rheumatoid arthritis, the potential clinical applications in precision medicine - Zhang, Haifeng; Ye, Yuna; Ling, Xingyan; Hambly, Brett D.; Bao, Shisan (Frontiers in Immunology, 2025)
Rheumatoid arthritis (RA) is a chronic, autoimmune inflammatory disorder that primarily affects the joints, and in severe cases, can damage other major organs, particularly in susceptible individuals. Management of RA primarily relies on disease-modifying anti-rheumatic drugs (DMARDs) often used in conjunction with low-dose steroids; however, outcomes are frequently suboptimal, resulting in significant physical and psychological impact. Biological agents have shown promise for non-responsive RA patients. Nevertheless, the precise underlying mechanism of RA remains unclear. Systemic and local levels of IL-37 and IL-38, anti-inflammatory cytokines, are elevated in RA patients. Intriguingly, these levels decrease in individuals experiencing remission, correlating with the Disease Activity Score (DAS28) and histopathological findings. In animal models, exogenous IL-37 and IL-38 demonstrate protective effects against RA development, while depletion of either cytokine exacerbates the disease in vivo. These findings suggest that the elevated IL-37 and IL-38 represent a compensatory response to the substantial inflammation in affected joints, attempting to mitigate dysregulated host immunity, albeit unsuccessfully. These data offer potential insights for developing novel, more effective RA therapies through precision medicine approaches.